Neutrophil activation in Behcet's disease - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2001)
Objective: Neutrophils are implicated in the pathogenesis of Behcet's disease (BD). Various functions of neutrophils are studied to clarify this role. Methods: The oxidative burst and phagocytic functions of neutrophils and surface molecules associated with neutrophil activation (CD10, CD14 and CD16) were investigated in BD patients by flow cytometric methods. Patients with inflammatory arthropathies, sepsis and healthy controls were also studied. Results In the oxidative burst experiments, after fMLP and PMA stimulation, stimulation index was found to be significantly decreased in patients both with BD and sepsis compared to healthy, controls and inflammatory arthropathies (p < 0.001 and p < 0.01, respectively). The phagocytosis of labelled E.coli particles in patients with BD was not different from that of the healthy controls, while it was decreased in diseased controls (p < 0.001). The surface density, of neutral endopeptidase (CD10) and the mean percentage of LPS receptor (CD14) was found to be significantly! higher in both BD patients and diseased controls (p < 0.001). The mean percentage of CD16 expression was only low in patients with sepsis (p < 0.001), whereas CD16 intensity on cells was found to be lower in patients with BD as well as in sepsis (p < 0.01). Conclusion These findings indicate the presence of in vivo pre-activated neutrophils in BD. A similar activation was also a feature of severe inflammatory disorders.
Keywords: Behcet's disease; neutrophils; CD10; CD14; CD16; phagocytosis; oxidative burst; FC-GAMMA-RIII; NEUTRAL ENDOPEPTIDASE; SUPEROXIDE GENERATION; BLOOD; CD14; LIPOPOLYSACCHARIDE; MIGRATION; LEUKOCYTES; EXPRESSION; ADHESION